Elucidation of the involvement of p14, a sperm protein during maturation, capacitation and acrosome reaction of caprine spermatozoa. - Pinki Nandi (Public Library of Science (PLoS), 2012)
Mammalian sperm capacitation is an essential prerequisite to fertilization. Although progress is being made in understanding the physiology and biochemistry of capacitation, little has been yet explored about the potential role(s) of individual sperm cell protein during this process. Therefore elucidation of the role of different sperm proteins in the process of capacitation might be of great importance to understand the process of fertilization. The present work describes the partial characterization of a 14-kDa protein (p14) detected in goat spermatozoa using an antibody directed against the purified protein. Confocal microscopic analysis reveals that the protein is present in both the intracellular and extracellular regions of the acrosomal and postacrosomal portion of caudal sperm head. Though subcellular localization shows that p14 is mainly cytosolic, however it is also seen to be present in peripheral plasma membrane and soluble part of acrosome. Immuno-localization experiment shows change in the distribution pattern of this protein upon induction of capacitation in sperm cells. Increased immunolabeling in the anterior head region of live spermatozoa is also observed when these cells are incubated under capacitating conditions, whereas most sperm cells challenged with the calcium ionophore A23187 to acrosome react, lose their labeling almost completely. Intracellular distribution of p14 also changes significantly during acrosome reaction. Interestingly, on the other hand the antibody raised against this 14-kDa sperm protein enhances the forward motility of caprine sperm cells. Rose-Bengal staining method shows that this anti-p14 antibody also decreases the number of acrosome reacted cells if incubated with capacitated sperm cells before induction of acrosome reaction. All these results taken together clearly indicate that p14 is intimately involved and plays a critical role in the acrosomal membrane fusion event.